AN EVALUATION OF GREEN BANKING IMPLEMENTATION: IMPACTS ON FINANCIAL PERFORMANCE AND SUSTAINABILITY REPORTING QUALITY IN THE INDONESIAN BANKING SECTOR - Fania Naomi Hutauruk; Sari Wahyuni (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
The implementation of Green Banking (GB) in Indonesia, institutionalized through OJK Regulation No. 51/2017, represents a strategic pivot towards integrating Environmental, Social, and Governance (ESG) principles to advance the nation's sustainable development agenda. This study provides a comprehensive evaluation of the influence of GB implementation on financial performance—measured by Return on Assets (ROA), Return on Equity (ROE), and Non-Performing Loans (NPL)—and on the quality of sustainability reporting (SR). The research further investigates the mediating roles of Green Innovation (GI) and Corporate Reputation (CR), alongside the moderating effects of Corporate Governance (CG) and Institutional Ownership (IO). Adopting a sequential explanatory mixed-methods approach, the study first conducts a quantitative analysis of panel data from 16 leading Indonesian banks over the 2019–2023 period. The subsequent qualitative phase deepens these findings through in-depth interviews with 12 senior practitioners from five of the sampled banks. Quantitative results reveal that GB significantly and positively influences financial performance, as measured by ROA (β=0.4278, p=0.0190) and ROE (β=0.4052, p=0.0038), and also enhances SR quality (β=0.5853, p=0.0026). However, contrary to the hypothesis, GB was found to significantly increase NPL (β=0.4085, p=0.0271), indicating a rise in credit risk. The findings on mediation show that GI significantly mediates the relationship between GB and ROA (Sobel test p=0.0409) as well as NPL (p=0.0372), but not ROE (p=0.055). Conversely, CR does not significantly mediate the link between GB and SR quality (p=0.052). For moderation, CG is confirmed to significantly strengthen the positive relationship between GB and both ROA (p=0.0017) and ROE (p=0.0048). However, the moderating effect of CG on the GB-NPL relationship and the moderating influence of IO on the GB-SR relationship were not supported (p>0.05). Qualitative findings uncover the complex dynamics of GB implementation, including challenges in green credit allocation, pressure from short-term-oriented foreign shareholders, and strategic mitigation through the fortification of governance via sustainability committees. This research contributes theoretically by testing a hybrid mediation-moderation model. Practically, it offers actionable recommendations for regulators (OJK) and the banking industry to enhance regulatory incentives, safeguard green innovation, and optimize institutional ownership structures to accelerate Indonesia's sustainable finance transition.